Co3O4 Nanoneedle Array Grown on Carbon Fiber Paper for Air Cathodes towards Flexible and Rechargeable Zn–Air Batteries - Ziyuan Li; Wenjia Han; Peng Jia; Xia Li; Yifei Jiang; Qijun Ding (Nanomaterials, 2021)
An economical and efficient method is developed for preparing flexible cathodes. In this work, a dense mesoporous Co3O4 layer was first hydrothermally grown in situ on the surface of chopped carbon fibers (CFs), and then carbon fiber paper (Co3O4/CP) was prepared by a wet papermaking process as a flexible zinc-air battery (ZAB). The high-performance air cathode utilizes the high specific surface area of a single chopped carbon fiber, which is conducive to the deposition and adhesion of the Co3O4 layer. Through the wet papermaking process, Co3O4/CP has ultra-thin, high mechanical stability and excellent electrical conductivity. In addition, the assembled ZAB exhibits relatively excellent electrochemical performance, with a continuous cycle of more than 180 times at a current density of 2 mA·cm−2. The zinc-air battery can maintain a close fit and work stably and efficiently even under high bending conditions. This process of combining single carbon fibers to prepare ultra-thin, high-density, high-conductivity carbon fiber paper through a papermaking process has huge application potential in the field of flexible wearables.